Design of an energy sharing adjustable speed drive system for dual-escalator applications - Ali Akbar Pammu (2013)
This final year project is one of the requirements to obtain the degree, bachelor engineering. This project aims to develop the dual sharing energy system in escalators by doing software simulation. DAB has been successfully evaluated and implemented in sharing energy system via DC/DC converter. Various topology of DAB DC/DC converter have been studied and the best topology was chosen is [2]. It is controlled by dual phase shift controller. The result of DAB simulation is also presented in this project.